Propaga??o e conserva??o in vitro de Martianthus leucocephalus (MART. ex BENTH.) J.F.B. PASTORE - Nepomuceno, Cristina Ferreira (2012)
Martianthus leucocephalus (Mart. ex Benth.) J.F.B. Pastore (Lamiaceae) is an aromatic medicinal specie, endemic to the semiarid Northeast, has economic importance due to their pharmacological potential. This work aimed to study the in vitro propagation of the specie Martianthus leucocephalus developing a protocol for in vitro micropropagation and conservation, allowing the establishment of strategies for their conservation and sustainable. In vitro establishment were carried out: 1 - test of different culture media (MS, MS ?, WPM, Agar and Paper germtest) in vitro germination; 2 - test of different medium culture (MS, MS ? and WPM) on growth In vitro and 3 ? assessement of different volumes of culture medium (in 500mL flasks) on in vitro growth of M. leucocephalus. In the process of morphogenesis in vitro, test: 1 - different types of explants (leaf segment, segment internodal and nodal) associated with different cytokinins (BAP, KIN and TDZ) 2 - combination of different concentrations of BAP and NAA; 3 - different explants at this position as the starting material, 4 - carbon sources (sucrose, maltose, fructose, lactose and glucose); 5 - organogenic potential from petioles sheets subjected to different cytokinins (KIN, BAP , TDZ and ZEA). For acclimatization, the plants have undergone a hardening process, which were used in various closures for tubes. In the greenhouse, plants were transferred to plastic cups containing potting soil, being covered with type pet bottles with lids, three days after the covers were desenroscadas, taken in the tenth and twenty-first day the bottles were removed completely. For the experiment of induction of somatic embryogenesis, we used segments of leaves under different concentrations of 2,4-D and KIN was determined from the growth curve of the fresh callus until the 90th day of culture at intervals of nine days. Carbohydrates were identified and quantified by HPLC. For histological studies, samples were fixed 70% FAA and prepared for analysis by optical microscope, with embedment in historesin. Histological sections were stained with toluidine blue (1%). For in vitro conservation Two experiments were conducted: 1 - we used the plant growth: ancymidol or paclobutrazol (0.0, 0.85, 1.7, 3.4 and 6.8 ?M) and 2 - was evaluated different agents osmotic (sucrose - Sac, mannitol - Man and sorbitol - Sor) and different concentrations (87.64, 131.46, 176.28, 219.10 and 262.92 mM). Osmotic agents mannitol and sorbitol were used in combination with sucrose. The in vitro germination of M. leucocephalus should be performed in culture medium MS?; chemical sterilization is an effective method for the in vitro culture of two species object of study of this work, the MS medium is the most suitable for the in vitro culture of M. leucocephalus and can be used is 60mL of medium in 500 ml flasks. Only the nodal segment showed morphogenetic response, and cytokinins promoted low rate of multiplication. The multiplication of shoots can be performed with 1.34 ?M of ANA from nodal segment, sucrose should be maintained as the best carbon source for the morphogenesis of M. leucocephalus, since the alternative carbon sources according to variables not outweigh sucrose as the multiplication of shoots. Organogenesis from leaf petiole with this potential organogenic shown, but it is necessary to test other culture media to favor higher regeneration of explants. The seedlings can be acclimatized without having to go through the process of hardening. Embryogenic calli were induced with 1?M 2,4-D + 0.5 ?M KIN, it was possible to identify the five stages of callus growth during the incubation period of embryogenic calli identified three carbohydrates: glucose, fructose and sucrose . At nine days incubation verified the presence of globular embryos whose ontogeny occurred from the vascular system and detected the greatest glucose content at 9 and 18 days of incubation. The paclobutrazol and ancymidol promoted decrease in plant growth, however the rate of survival at 240 days was below the results obtained with the osmotic agents. The conservation in vitro M. leucocephalus can be carried out in culture medium supplemented with Sac + 43.82 43.82 mM mM mM Man or Sac + 65.73 65.73 mM Man, since these treatments promoted survival rate of approximately 80%, while reducing the length of shoots, number of leaves, number of senescent leaves and promoted gain in dry matter of the shoot.